2022
DOI: 10.1108/ajim-07-2022-0344
|View full text |Cite
|
Sign up to set email alerts
|

Job demands and technology overload influencing work stress in organizations during the COVID-19 pandemic

Abstract: PurposeThis study is based on the stimulus–organism–response (SOR) model to examine how job demands and technology overload affect work stress for workers using video conferencing apps (VCAs) in organizations during the COVID-19 pandemic. Moreover, the moderating effect of technology self-efficacy was tested in the model on the relationship between technology overload and work stress.Design/methodology/approachAn online survey was conducted to investigate workers on PTT forums in Taiwan. A sample was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Another study examined the relationship between self-efficacy and information overload in the context of social media use. The study found that self-efficacy had a negative relationship with information overload, indicating that individuals with higher levels of self-efficacy were less likely to experience information overload [ 74 ]. While these studies do not directly investigate the moderating effect of self-efficacy on the relationship between addiction, service overload, information overload, cognitive dissonance, and discontinuous usage intention, they suggest that self-efficacy may play a role in these relationships.…”
Section: Research Hypotheses and Modelmentioning
confidence: 99%
“…Another study examined the relationship between self-efficacy and information overload in the context of social media use. The study found that self-efficacy had a negative relationship with information overload, indicating that individuals with higher levels of self-efficacy were less likely to experience information overload [ 74 ]. While these studies do not directly investigate the moderating effect of self-efficacy on the relationship between addiction, service overload, information overload, cognitive dissonance, and discontinuous usage intention, they suggest that self-efficacy may play a role in these relationships.…”
Section: Research Hypotheses and Modelmentioning
confidence: 99%